Functional abilities, physical pain and non-communicable chronic diseases in retired teachers in Daraa city: Self-reported descriptive study (Damascus University Journal of educational and Psychologyical sciences, 2026)
Descriptive study aimed to identify the limitations of functional abilities, and detect the percentages of chronic non-communicable diseases (NCDs) and chronic pain, and to illustrate the complex of weight and the prvalence of NCDs in retired teachers. Sample confined to retired teachers in Daraa city, where its number was 67 teachers, which from 37 were females and 30 were males. Collecting data was based on self-rported questionaire, which incleded demographic information, and questions related to functional abilities and chronic pain and NCDs. Results revealed that 68% of our sample was belonged to overweight and obesity classification, and 62.7% have stated that they have weak or absent functional abilityK from those, 17.9% had at least one and 20.9% had two and 23.9% had three. Additionally, 56.7% have specified that they have NCD, from those, 17.9% had at least one and 16.4% had two and 16.4% had three and 7.5% had four NCDs. Finally, 73.1% from our sample participants have also identified that the have chronic pain, from those, 37.3% have chronic pain in one body region, and 35.4% have chronic pain in two regions.
Keywords: Functional Abilities; Chronic Pain; Ncds